APAKAH MINAT BELI KONSUMEN DAPAT MENUNJANG KEPUTUSAN PEMBELIAN MELALUI SERVICE QUALITY? - Antara, Made Ermawan Yoga; Martini, Ida Ayu Oka (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
Purchasing decisions are the ultimate goal of establishing a business to be able to dominate the market and gain profits from the business. Purchasing decisions themselves are influenced by several factors, including store atmosphere, quality service and buying interest. The purpose of this research is to determine the determining factors for purchasing decisions based on consumer perceptions at Tenun Endek Tinizhop. This research was conducted at Tenun Endek Tinizhop which is located on Jalan Kembang Matahari I Denpasar Bali, by distributing 200 questionnaires to Tenun Endek Tinizhop consumers. This research is quantitative research with data collection using the questionnaire method. Research findings show that purchasing interest and purchasing decisions are significantly positively influenced by store atmosphere. Furthermore, purchasing decisions and purchasing interest are influenced by service quality in a significantly positive way. The results of the mediation test show that the relationship between store atmosphere and service quality on consumer purchasing decisions at Tenun Endek Tinizhop is significantly mediated by purchase interest. This research is quantitative research with data collection using the questionnaire method. The results of this research show that store atmosphere has a significant positive effect on purchasing interest and purchasing decisions. Furthermore, service quality has a significant positive effect on purchasing decisions and purchasing interest. The results of the mediation effects research show that purchase interest has a significant influence or strengthens the relationship between store atmosphere and quality service on consumer purchasing decisions at Tenun Endek Tinizhop